See you next Christmas [videorecording (DVD)] - Weatherup, Christine, 1983-; Chahin, Beatriz; Enlow, Matt; Guest, Elizabeth; Meijer, AJ; Vescio, Vin (Rekon Productions, 2021)
"Annie and Tom Clark throw a holiday party every year, "Clarkmas." Over the years, it's become the go-to holiday event for their ragtag group of friends. When chronically single Natalie and Logan continue to run into each other at the party year after year, they begin to wonder if maybe they're meant to be together."--Container.